Engagement melalui Teka-Teki Silang: Crossword Puzzle sebagai Strategi Literasi Informasi Pemustaka - Andina, Syifa; Masruri, Anis (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
Information Literacy has an important role in the school environment. Information Literacy is closely related to libraries and librarians. The main concern of librarians in developing information literacy programs is because Indonesia is ranked 60th out of 61 countries regarding interest in reading according to data from the most littered nation in the world in 2016. Libraries and librarians can develop the Brain Teaser Games Method using crossword puzzles through literacy programs and school library information. This research intends to determine how this method is implemented for users and school libraries. The research method used is a type of qualitative descriptive research in a literature review which is then used to collect data or sources related to the topic raised in a study. The results of the research can conclude that the crossword puzzle method is useful for readers. Readers' interest in reading has increased, because students are enthusiastic about crossword puzzles. The crossword puzzle method also has an impact on increasing the number of library visitors and improving the quality of librarian competence in conveying information lies to users.